Current practices in epilepsy monitoring units (EMU) in India. (December 2021) - Baheti, Neeraj; Rathore, Chaturbhuj; Bansal, Atma Ram; Kannan, Lakshminarayanan; Gopinath, Siby; Pillai, Ashok; Jagtap, Sujit; Patil, Sandeep; Jabeen, Shaik Afshan; Suryaprabha, Turaga; Jayalakshmi, Sita; Ravat, Sangeeta; et al.
Highlights: We conducted a survey of practices in 51 epilepsy monitoring units (EMUs) in India. One-third of the EMUs in India do not have standard safety practices and protocols. Public hospitals have long waiting periods for prolonged Video-EEG monitorings. With 52 EMUs for 1.3 billion people, India has severe shortage of EMUs. Study provides information about the current status of EMUs in developing countries. Abstract: Aim: As an initial step to develop guidelines for epilepsy monitoring units (EMUs) appropriate for developing countries, we inquired the existing practices in EMUs in India. Methods: After checking for the content and face validity as well for clarity, we sent a 52-item online non-anonymized questionnaire to all the 52 EMUs in India. Results: The questionnaire was completed by 51 of the 52 EMUs (98% response rate). The majority of the EMUs are located in major cities and 51% are located in non-governmental corporate hospitals. There are total of 122 prolonged video-EEG monitoring (PVEM) beds in India and 70% EMUs have ≤2 beds. Approximately two-thirds of the EMUs have defined protocols for pre-procedure consent and risk assessment, management of seizure clusters and status epilepticus, continuous observation of patients, and peri‑ictal testing. Only one-third of the EMUs have protocols for management of post-ictal psychosis, anti-suffocation pillows, and protected environment within bathrooms. The waiting period for PVEM is more (49.9 ± 101 vs. 4.9 ± 10.9 days; p = 0.04) and mean cost for 3-day PVEM is less (INR 8311 ± 9021 vs. 30, 371 ± 17, 563; p <0.0001) in public as compared to private hospitals. There was a negative correlation between cost of PVEM and the waiting period ( r =-0.386; p = 0.01). Safety practices are similar in public and private hospitals. Conclusions: Although practices in EMUs in India vary widely, they are comparable to those in developed countries. India has severe shortage of EMUs and long waiting lists for affordable PVEM.